A modified-mxEWMA location chart for the improved process monitoring using auxiliary information and its application in wood industry. Issue 5 (2nd September 2020) - Anwar, Syed Masroor; Aslam, Muhammad; Ahmad, Shabbir; Riaz, Muhammad
ABSTRACT: In this paper, we have proposed a new modified Exponentially Weighted Moving Average location control chart named as a modified-mxEWMA chart. The newly proposed chart uses the information of an auxiliary variable to improve the shift detection ability. The control structure of the modified-mxEWMA chart is developed and important measures such as ARL, SDRL, EQL, PCI, and RARL are computed to assess the performance of the proposed chart. A comparative analysis is carried out among the proposed modified-mxEWMA chart and some existing competitive EWMA charts. The results obtained from this study revealed that the proposed chart performs very well for the monitoring of small to moderate shifts in the process location relative to the existing control charts. Finally, a real-life data set from the wood industry is used to show the implementation procedure of the proposed chart in real applications.